2009
DOI: 10.1021/jf900039s
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Turkish Honeys to Determine Authenticity Using Physical and Chemical Characteristics

Abstract: Seventy authentic honey samples of 9 different floral types (rhododendron, chestnut, honeydew, Anzer (thymus spp.), eucalyptus, gossypium, citrus, sunflower, and multifloral) from 15 different geographical regions of Turkey were analyzed for their chemical composition and for indicators of botanical and geographical origin. The profiles of free amino acids, oligosaccharides, and volatile components together with water activity were determined to characterize chemical composition. The microscopic analysis of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 26 publications
4
60
0
15
Order By: Relevance
“…The chemical composition of honey is studied and known to a large extent for nearly 50 years. The presence of compounds beneficial to health for their antioxidant properties or for other reasons is well known, this is the case of polyphenols [68][69][70][71][72][73][74] or amino acids [75][76][77][78][79][80][81][82][83], some of them are good fluorophores like polyphenols. Works evoke the interest of using these fluorophores as tracers of the floral origin of honeys.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition of honey is studied and known to a large extent for nearly 50 years. The presence of compounds beneficial to health for their antioxidant properties or for other reasons is well known, this is the case of polyphenols [68][69][70][71][72][73][74] or amino acids [75][76][77][78][79][80][81][82][83], some of them are good fluorophores like polyphenols. Works evoke the interest of using these fluorophores as tracers of the floral origin of honeys.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous of these compounds including: 2-ethyl-1-hexanol, 1-octanol, 1-nonanol, furfural, benzaldehyde, octanal, decanal, benzeneacetaldehyde, heptane, 1-octene, octane, nonane, 2,5-dimethyl-furan, borneol, 3,4,5-trimethyl-phenol, have been identified in Greek and Turkish pine honeys [19,20] as well as in fir honeys from Croatia [21]. What is remarkable is that, the ethyl esters identified in the present study, have not been reported previously in monofloral honeys produced in different countries [3,20,21,22]. These compounds are reported for the first time in fir honey, and may originate from resins secreted in Greek fir trees.…”
Section: Volatile Compounds Of Commercial Fir Honeysmentioning
confidence: 99%
“…It should be stressed that, honey aroma, along with colour and taste, are among of the most important parameters affecting product acceptability by consumers. Furthermore, numerous volatile markers have been used for the determination of geographical and botanical origin of particular honey samples [2,3,4,20], using chemometrics. Table 3.IS: internal standard.…”
Section: Volatile Compounds Of Commercial Fir Honeysmentioning
confidence: 99%
“…An assessment of honey authenticity, especially determination of its botanical origin, based on the content of amino acids, has been the subject of a number of studies (60)(61)(62)(63)(64)(65)(66). Some of them emphasised that specific amino acid profile may be used for the assessment of honey authenticity (60)(61)(62), while other reports stated that such discrimination was incomplete and could be used for an unambiguous assignment only together with other parameters such as physicochemical ones, sugar and mineral content, etc.…”
Section: Authenticity Of Serbian Honeymentioning
confidence: 99%